A dimensão social dos processos de integração regional: as estratégias do Mercosul e da União Europeia - Garcia, Valeria Paola Vetuschi (2007)
Globalization is a complex process that generated the instauration of a new global order, in which the State-nation becomes weakened and its autonomy and abi city, uncertain. From a sociological point of view, globalization is increasingly approaching the communities and the States of the world. The initiatives of economic regionalization appear as a reply to the globalization process. People are living, since the beginning of the second half of the past century, the gradual sprouting of regional communities that, under the integration figure, try to decrease its differences to get the necessary unit that will allow them to enter in a global commercial system. However, if these associations will only be thought as a mechanism to increase the competitiveness in the global free market, its intention is only to increase the advantages for the countries which are most prepared for international competition. Nonetheless, economic globalization has caused the deepening of the social differences and the exclusion of significant part of the populations, independently of the development condition of each country. Thus, although the integration processes have an eminently economic origin, the social dimension has been noticed, once it is not possible to ignore the interrelation between economic and social dimensions, which is as harmful as to ignore the importance and the necessity of combating social exclusion, attacking its causes. In this context, social dimension of the integration process is an expression which involves three aspects: the attention to the negative social effects of the integration, the articipation of the civil society in the process and the distribution of the countries social debt whose priority is to take care of the poverty and the social exclusion that affect great sectors of the population. However, the social dimension of the regional integration processes develops much more as a demand of the proper involved societies, as a requirement of the social actors, what as a proper result of the integrationist process or the will of its articulators. As in the European Union as in the Mercosul, the mechanisms that articulate the strategies of social inclusion are allaying, as an attempt to decrease the discontentment of the public opinion in the societies involved. The European Social Letter of 1961, the Communitarian Letter of the Workers Basic Rights of 1989 and the Mercosul Sociolaboral Declaration of 1998, are examples of this. The Social Letters can be defined as solemn declarations in which the States proclaim certain rights and recognize goals, labor or social objectives in common. But, the European and the Mercosul Social Letters are unprovided of legal effectiveness: they are mere ethical declarations of principles or mere lines of social politics direction implemented by the block. Without a character link, its achievement is left to the free will of the States. Analyzing the social dimension of both processes, it is verified that basically there is a concern with the job generation, but it seems that the social matters are ignored